Impact of climate change on the ground thermal regime in the lower Lena region, Arctic central Siberia - Konstantinov, Pavel Y.; Basharin, Nikolay I.; Fedorov, Alexander N.; Iijima, Yoshihiro; Andreeva, Varvara A.; Semenov, Valerii P.; Vasiliev, Nikolay F. (Land)
This paper presents the results of 30 years of permafrost thermal monitoring in the Tiksi area in the eastern Russian Arctic. At a stone ridge site, the mean annual temperatures in the upper 30 m of the ground have increased by 1–2.4 C compared to the first years of observations, with trends of C/yr. At the same time, its change was uneven. In the last 20 years, the rate of increase has increased compared with the first decade of observations. At wet tundra sites in the foothill plain, the mean annual temperatures at the top of permafrost have increased by 2.4–2.6 C between 2005 and 2022 at rates of 0.11–0.15 C/yr, and the active layer thicknesses have increased at rates of 0.05–0.41 cm/yr.